Bridging the gap: understanding the factors affecting pedestrian safety perceptions in the age of driverless vehicles - Saki Rezwana; Mohammad Razaur Rahman Shaon; Nicholas Lownes; Eric Jackson (Traffic Safety Research)
he advent of autonomous technologies necessitates a deeper understanding of pedestrian behavior and safety in environments where pedestrians need to interact with driverless vehicles (DV). Our study explores how pedestrians perceive and react to DVs compared with Human-Driven Vehicles (HDV), focusing on objective measures such as gap acceptance (GA) and psychophysiological indicators like Electro-dermal Activity (EDA). Structured in three phases, the study comprises a preliminary questionnaire to gauge public perception, followed by immersive virtual reality (VR) simulations that mimic real-world traffic scenarios within a VR environment, and concludes with a post-experiment survey. The simulation experiment was designed to analyze pedestrian responses to varying traffic scenarios developed using DVs and HDVs, measuring EDA to assess emotional and stress responses leading to changes in the gap acceptance behavior. The study employed hypothesis testing to assess DV's impact on pedestrians' psychophysiological reactions that can lead to changes in pedestrian behavior. This study also explored the effect of education level and perception of pedestrians towards automation technology that may influence outcomes. The analysis of EDA showed higher stress levels in scenarios involving DVs measured using the Galvanic Skin Response component. This result heightened stress response may be attributed to the unpredictability and novelty of DVs. The analysis with gap acceptance (GA) time revealed significant differences in GA times across traffic scenarios. Pedestrians exhibited longer GA times with DVs than HDVs, suggesting cautious crossing behavior. Our results underscore the impact of traffic scenarios on pedestrian behavior and stress levels, highlighting the influence of driverless technology on pedestrian dynamics.